Cetaceans as sentinels for informing climate change policy in UK waters. (September 2021) - Williamson, Michael J.; ten Doeschate, Mariel T.I.; Deaville, Rob; Brownlow, Andrew C.; Taylor, Nicola L.
Abstract: Climate change is predicted to have profound consequences for marine ecosystems. Due to the growing political and social drive to address its impacts, monitoring and mitigating climate change is a priority in marine policy in the UK. Cetaceans have been proposed as informative sentinel species for monitoring ocean health. Here, strandings data from four UK cetacean species were assessed for their use as a tool to aid policy makers monitoring climate change in marine environments. Data on stranded cetaceans were collected from 1990 to 2018 and differences in the proportions of stranded cold water adapted and warm water adapted species assessed using Generalised Linear Models (GLM), with 6-year periods and four regions of the UK included as explanatory variables. This modelling approach showed an increase in the proportion of stranded warm water adapted species over time across the UK and that differences in proportion of strandings between cold water and warm water adapted species can be detected between regions and 6-year periods, chosen as metrics to coordinate with reporting cycles for policy assessment needs. As such, these results show the potential for utilising strandings data to identify changing oceanic trends at the appropriate spatial and temporal scales for policy reporting in the UK. However, development of these analyses with a more detailed examination of these data at a finer resolution, incorporating other data sources, such as distribution trends and dietary stable isotope data, may be required before it is applicable as an indicator for trends in changes in climate.